It comes from the sea: macroalgae-derived bioactive compounds with anti-cancer potential - Nova, Paulo (2023)
Nature derived compounds represent a valuable source of bioactive molecules with enormous potential. The sea is one of the richest environments, full of skilled organisms, where algae stand out due to their unique characteristics. Marine macroalgae adapt their phenotypic characteristics, such as chemical composition, depending on the environmental conditions where they live. The compounds produced by these organisms show tremendous potential to be used in the biomedical field, due to their antioxidant, anti-inflammatory, immunomodulatory, and anti-cancer properties. Cancer is one of the deadliest diseases in the world, and the lack of effective treatments highlights the urgent need for the development of new therapeutic strategies. This review provides an overview of the current advances regarding the anti-cancer activity of the three major groups of marine macroalgae, i.e., red algae (Rhodophyta), brown algae (Phaeophyceae), and green algae (Chlorophyta) on pancreatic, lung, breast, cervical, colorectal, liver, and gastric cancers as well as leukemia and melanoma. In addition, future perspectives, and limitations regarding this field of work are also discussed.